Cardioprotective Effect of Paeonol on Chronic Heart Failure Induced by Doxorubicin via Regulating the MiR-21-5p/SKP2 Axis - Chen, Cong; Liu, Shuhong; Cao, Gaozhen; Hu, Yang; Wang, Run; Wu, Min; Liu, Mingya; Yiu, Kai Hang (Frontiers in Cardiovascular Medicine, 2022)
Background: Considering the cardioprotective effect of Paeonol on epirubicin-induced cardiac injury, this study primarily explored the role of Paeonol in doxorubicin (DOX)-induced chronic heart failure (CHF). Methods: DOX-induced CHF-modeled rats were treated with Paeonol. Rat cardiac function and myocardial damage were evaluated by the multifunction instrument, and the histopathology, apoptosis, and the expressions of miR-21-5p and S-phase kinase associated protein 2 (SKP2) in myocardium were detected. The target gene of miR-21-5p was confirmed by dual-luciferase reporter assay. After the required transfection or Paeonol treatment, the viability, apoptosis, mitochondrial membrane potential (MMP), reactive oxygen species (ROS) of the DOX-induced cardiomyocytes were determined. RT-qPCR and western blot were performed to quantify the expressions of miR-21-5p, SKP2, and apoptosis-related factors. Results: Paeonol improved cardiac function and also ameliorated the cardiac damage of CHF-modeled rats, where the down-regulation of abnormally elevated myocardial damage markers, including brain natriuretic peptide, lactate dehydrogenase, renin, angiotensin II, aldosterone, and endothelin 1, was observed. Paeonol alleviated the histopathological injury and suppressed the apoptosis in CHF-modeled rats, inhibited miR-21-5p expression, and up-regulated SKP2 expression in vitro and in vivo. MiR-21-5p targeted SKP2. Paeonol and SKP2 increased the viability and MMP, but reduced apoptosis and ROS in the DOX-induced cardiomyocytes. MiR-21-5p exerted effects opposite to PAE and SKP2, and it down-regulated the expressions of Bcl-2 and mitochondrion-Cytochrome c (Cyt c), and up-regulated the expressions of Bax, C-caspase-3, and cytoplasm-Cyt c. MiR-21-5p reversed the effects of Paeonol and its effects were further reversed by SKP2. Conclusion: Paeonol shows a cardioprotective effect on DOX-induced CHF via regulating miR-21-5p/SKP2 axis.